Impact of Community-Based Oral Health Education Programs on Periodontal Disease Awareness and Prevention - Muhammad Junaid Hashmi, Hussain Mujtaba Malik, Saleem Adil, Shabir Ahmad, Muhammad Sami Iqbal, Hammal Khan Naseer Baloch (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Community-based oral health education programs have emerged as a promising strategy toenhance periodontal disease awareness and prevention. This experimental study evaluated theimpact of a structured three-month interactive education intervention on periodontal knowledge